A novel technique for induction heating dryer with temperature and voltage control for power inverter - Jeerapong Srivichai; Kittaya Somsai; Akkachai Phuphanin; Nithiroth Pornsuwancharoen (Institute of Advanced Engineering and Science, 2026)
This study presents a novel prototype of an induction heating dryer integrating hysteresis control with phase-shifted pulse width modulation (PWM) for the first time. The system replaces conventional resistance heating, improving energy efficiency and thermal stability. The 2 kW prototype comprises a drying chamber and a hot air unit with controlled airflow of 1.5 m/s. Phase angle adjustment reduces voltage, current, and power consumption while maintaining the power factor within acceptable limits. The temperature control maintains stability within ±1 °C of the setpoint. The results demonstrate fast, energy-efficient, and precise drying, offering potential benefits for food processing and textile industries, and providing a foundation for future development of intelligent, energy-efficient induction dryers.